VIETNAMESE FERMENTED PLANTS LACTOBACTERIA ANTAGONISTIC ACTIVITY - Ж. Ю. Сергєєва; О. В. Басюл; О. Г. Горшкова; Т. І. Гаврилюк; А. М. Назаренко (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2016)
The aim of the research was to identify and study antagonistic properties of lactic acid bacteria isolated from vietnamese fermented plant products. Materials and methods. Lactobacillus genus bacteria strains were isolated from vietnamese uncommercial autofermented savory products. Five Lactobacillus strains were checked for the antagonistic properties presence against 12 strains of phytopathogenic bacterium Erwinia carotovora. Lactobacillus genus bacteria antagonistic activity in vitro research was performed by agar holes. Antagonistic bacteria in vivo interaction modeling system with pathogens was carried out on Solanum tuberosum potato tubers and Daucus carota carrots. Lactobacilli strains identification was performed using API-systems. Results and discussion. Selected Lactobacillus strains were identified as L. paracasei ONU 520, L. brevis ONU 521, L. plantarum ONU 522, L. plantarum 523 ONU, L. rhamnosus ONU 524 based on tinctirial, morphological and biochemical properties. It was found that in 24 hours of cultivation around the agar holes into which the antagonistic strains culture liquid had been introduced there were formed the growth inhibition zones up to 19 mm in diameter. It has been determined that antagonistic effect appeared due to the organic acids production by lactobacilli. It was found that the lactobacteria effectively compete phytopathogenic bacteria E. carotovora and in all cases inhibit their growth on carrot roots and in 80% on potato tubers. Lactobacterial strains mixture showed the same efficiency as individual strains. Conclusions. Lactobacillus genus bacteria strains, isolated from vietnamese uncommercial autofermented savory products, showed high levels of antagonistic activity against pathogenic Erwinia.